Temporal patterns of vampire bat rabies and host connectivity in Belize. Issue 2 (4th August 2020) - Becker, Daniel J.; Broos, Alice; Bergner, Laura M.; Meza, Diana K.; Simmons, Nancy B.; Fenton, M. Brock; Altizer, Sonia; Streicker, Daniel G.
Abstract: In the Neotropics, vampire bats ( Desmodus rotundus ) are the main reservoir host for rabies, a highly fatal encephalitis caused by viruses in the genus Lyssavirus . Although patterns of rabies virus exposure and infection have been well studied for vampire bats in South America and Mexico, exploring the ecology of vampire bat rabies in other regions is crucial for predicting risks to livestock and humans. In Belize, rabies outbreaks in livestock have increased in recent years, underscoring the need for systematic data on viral dynamics in vampire bats. In this study, we examine the first three years of a longitudinal study on the ecology of vampire bat rabies in northern Belize. Rabies seroprevalence in bats was high across years (29%–80%), suggesting active and endemic virus circulation. Across two locations, the seroprevalence time series per site were inversely related and out of phase by at least a year. Microsatellite data demonstrated historic panmixia of vampire bats, and mark–recapture detected rare but contemporary inter‐site dispersal. This degree of movement could facilitate spatial spread of rabies virus but is likely insufficient to synchronize infection dynamics, which offers one explanation for the observed phase lag in seroprevalence. More broadly, our analyses suggest frequent transmission of rabies virus within and among vampire bat roosts in northern Belize and highlight the need for future spatiotemporal, phylogenetic and ecological studies of vampire bat rabies in Central America.